2011
DOI: 10.1378/chest.10-2865
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Lung Disease, Macrocytosis, and Premature Graying in Kindreds With Telomerase (TERT) Mutations

Abstract: TERT mutation carriers exhibit early preclinical signs of lung fibrosis, bone marrow dysfunction, and premature graying. These clinical features and short telomere lengths characterize patients with germline TERT mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 33 publications
3
72
0
6
Order By: Relevance
“…This study extends these findings by showing that such abnormalities are also associated with increased respiratory symptoms, reduced total lung capacity, and reduced diffusion capacity of carbon monoxide in the general population. Our genetic-association study of interstitial lung abnormalities in the general population adds to studies of patients with familial interstitial pneumonia 22 and shows that at least some component of the genetic predisposition for interstitial lung abnormalities and idiopathic pulmonary fibrosis is shared. The common association between MUC5B genotype, idiopathic pulmonary fibrosis, 8 and now a phenotype in the general population that includes abnormalities on imaging, physiological abnormalities, and gasexchange abnormalities suggests that, in at least some cases, interstitial lung abnormalities may represent an early or subclinical stage of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 82%
“…This study extends these findings by showing that such abnormalities are also associated with increased respiratory symptoms, reduced total lung capacity, and reduced diffusion capacity of carbon monoxide in the general population. Our genetic-association study of interstitial lung abnormalities in the general population adds to studies of patients with familial interstitial pneumonia 22 and shows that at least some component of the genetic predisposition for interstitial lung abnormalities and idiopathic pulmonary fibrosis is shared. The common association between MUC5B genotype, idiopathic pulmonary fibrosis, 8 and now a phenotype in the general population that includes abnormalities on imaging, physiological abnormalities, and gasexchange abnormalities suggests that, in at least some cases, interstitial lung abnormalities may represent an early or subclinical stage of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 82%
“…Compared to matched family members without mutation, patients with TERT mutations have lower platelets count although generally within normal limits [17]. The co-occurrence of bone marrow failure and PF in the same individual or family is highly predictive of telomerase mutation [18].…”
Section: Discussionmentioning
confidence: 99%
“…None of the treatment was associated with any objective pulmonary improvement assessed either by CT scan or an increase in VC or DLCO by 10% of the predicted value or greater. At the last visit before transplantation, VC and DLCO were 42% [75-22] and 22% [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] of predicted, respectively.…”
Section: Clinical Characteristics At the Diagnosis Of Pulmonary Fibrosismentioning
confidence: 99%
“…• WBC count, hematocrit level, or platelet count below the lower limit of normal 13 • Mean corpuscular volume (MCV) above the upper limit of normal 14,15 • Abnormal liver function tests 11 • Abnormal coagulation profi le • History or evidence of hepatosplenomegaly on abdominal ultra sonography • Family history of interstitial pneumonia, self-reported early graying, aplastic anemia, or liver disease Individuals with suspected short telomeres then underwent telomere length testing. Th ey were diagnosed with short telomeres if telomere length was shorter than the 10th percentile of the reference population.…”
Section: Subjectsmentioning
confidence: 99%
“…Using the previously established criteria predictive of telomeropathy 14 described previously we prospectively assessed 22 patients with ILD being evaluated for lung transplantation and found that 15 (68.2%) had telomeres shorter than the 10th percentile predicted for age ( Table 1 ).…”
Section: Targeted Testing For Short Telomeres In a Cohort Of Patientsmentioning
confidence: 99%